The Influence of Profitability, Liquidity, Leverage, Gender Diversity, and Political Connections on Financial Distress (Empirical Study of Property and Real Estate Companies Listed on the Indonesian Stock Exchange 2020 - 2022) - Putri, Putu Talia Natasia; Badera, I Dewa Nyoman; Suryanawa, I Ketut (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Financial difficulties occur when a company's financial situation deteriorates, potentially leading to insolvency or liquidation. This study seeks to gather real-world evidence on how profitability, liquidity, debt levels, gender diversity, and political ties impact financial distress. The research focused on property and real estate companies listed on the Indonesia Stock Exchange between 2020 and 2022, with a sample size of 208. Sample selection followed purposive sampling methods. Data analysis was performed using logistic regression techniques with the SPSS software. Findings indicate that higher profitability and liquidity are associated with lower levels of financial distress. These results support agency and signal theories, providing empirical evidence on the link between profitability, liquidity, and financial distress. However, leverage, gender diversity, and political connections were found to have no significant impact on financial distress. Contrary to expectations, the study did not confirm agency, signal, or feminist theories. The practical implications of this research include offering a deeper understanding to scholars and readers, serving as a valuable resource for further studies on the subject.